Revalidação do gênero Demophoo (Coleoptera, Cerambycidae, Lamiinae) - Julio, Carlos Eduardo De Alvarenga [UNESP] (Museu de Ciências Naturais, 2003)
Demophoo Thomson, 1864 is removed from the synonymy of Hoplistocerus Blanchard, 1847. The genus and D. hammatus (Chabrillac, 1857) are redescribed.
Revalidation of the genus Demophoo (Coleoptera, Cerambycidae, Lamiinae)
Keywords: Cerambycidae; Anisocerini; Demophoo; taxonomy; Neotropical